2006
DOI: 10.1080/02786820600803917
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol Absorption Measurement using Photoacoustic Spectroscopy: Sensitivity, Calibration, and Uncertainty Developments

Abstract: Light absorption by aerosols is one of the most uncertain parameters associated with the direct and indirect aerosol effects on climate and is one of the most difficult quantities to measure. This article describes the development of a sensitive method of measuring aerosol absorption at 532 nm with excellent time response (detection limit: 0.08 Mm −1 , 60 second average) using photoacoustic absorption spectroscopy. An accurate calibration method (accuracy of 1-2%) at atmospherically relevant absorption levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
263
0
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 251 publications
(282 citation statements)
references
References 33 publications
15
263
0
4
Order By: Relevance
“…Photoacoustic spectroscopy (PAS) has become a popular technique for measuring absorption of light by atmospheric aerosols for PAS (Lack et al, 2006(Lack et al, , 2012, recent works exploring its validity have come to contradictory conclusions: Bluvshtein et al (2017) saw a discrepancy between ozone calibrations and particle-based calibrations, while Davies et al (2018) found this not to be the case. Concurrent to these publications, we have been exploring the use of ozone as a PAS calibrant for multipass, multi-wavelength, aerosol photoacoustic spectrometers; our observations are presented here to add to the discussion on the topic.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Photoacoustic spectroscopy (PAS) has become a popular technique for measuring absorption of light by atmospheric aerosols for PAS (Lack et al, 2006(Lack et al, , 2012, recent works exploring its validity have come to contradictory conclusions: Bluvshtein et al (2017) saw a discrepancy between ozone calibrations and particle-based calibrations, while Davies et al (2018) found this not to be the case. Concurrent to these publications, we have been exploring the use of ozone as a PAS calibrant for multipass, multi-wavelength, aerosol photoacoustic spectrometers; our observations are presented here to add to the discussion on the topic.…”
Section: Introductionmentioning
confidence: 94%
“…The PAS cell itself sits within the multipass cell and follows the design of Lack et al (2006). A calibrated photodiode behind the rear multipass mirror is used to monitor the power of each laser simultaneously.…”
Section: Photoacoustic Spectrometermentioning
confidence: 99%
See 1 more Smart Citation
“…While PSL falls in the ≤1% category for C(λ) A&O error, APSL error is likely >2% due to its SSA of 0.71-0.89 (Lack et al 2006;Flores 2011) and strong wavelength dependence. Since there is no error in the extrapolated cross-sections (due to extrapolating between two data points with two variables), error only stems from the variability of the nephelometer (1%), the uncertainty of the correction factor (1%, see Bond et al 2009), and the CPC error (10%).…”
Section: The Nephelometermentioning
confidence: 99%
“…3. The SSA of absorbing PSL with a comparison with measurements, by Lack et al (2006) and Flores (2011). Dotted lines or bars are the error (1s).…”
Section: Ssa Ab and Absorbing Pslmentioning
confidence: 99%